2013
DOI: 10.1007/s10921-013-0191-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Ultrasonic Monitoring of Splitting Failure in Reinforced Concrete

Abstract: This paper investigates inspection of reinforced concrete elements sensitive to the splitting failure. The behaviour of a reinforced concrete specimen subjected to a tensile stress is considered. The damage detection procedure is based on the ultrasonic wave propagation technique. The piezoelectric transducers are located on both ends of the specimen and the measurements are taken periodically during the incrementally increased loading. The features of measured signals in time and frequency domains as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…Moreover, an DAMAGE ANALYSIS OF TENSIONING CABLE ANCHORAGE ZONE OF A BRIDGE...application of structural health monitoring, as in e.g. [7] or [10], could give an answer to whether or not the numerical estimations are correct.…”
Section: Comparison Of Fem Results and In Situ Crack Patternsmentioning
confidence: 99%
“…Moreover, an DAMAGE ANALYSIS OF TENSIONING CABLE ANCHORAGE ZONE OF A BRIDGE...application of structural health monitoring, as in e.g. [7] or [10], could give an answer to whether or not the numerical estimations are correct.…”
Section: Comparison Of Fem Results and In Situ Crack Patternsmentioning
confidence: 99%
“…For greater depth, other methods should be used. 20 , 21 for example: acoustic waves are widely used 22 . …”
Section: Estimate the Water Level Using Terrestrial Laser Scanningmentioning
confidence: 99%
“…The advantage of wave propagation-based methods is that they may be used in automatic structural health monitoring (SHM) systems. It has been demonstrated that wave propagation methods can be efficiently applied in monitoring of the strain changes in reinforced concrete during the process of damage development [10][11][12][13]. Wave propagation signals collected during an experiment conducted on concrete structures are characterized by a greater degree of complexity than for steel thin rods [14] or plates [15] because of the solid geometry of typical concrete element.…”
Section: Introductionmentioning
confidence: 99%